Welcome :: Homework Help and Answers :: Mathskey.com
Welcome to Mathskey.com Question & Answers Community. Ask any math/science homework question and receive answers from other members of the community.

13,356 questions

17,804 answers

1,438 comments

35,964 users

If g(x) = 2x + 2, find g(a + h) - g(a)?

+1 vote
Pkease help!!!!!!!!!!!!!!!!!!!!!!!!
asked Jan 8, 2013 in ALGEBRA 1 by homeworkhelp Mentor

2 Answers

+1 vote
g(x)=2x+2

g(a)=2a+2                                                (just replace x in a)

g(a+h)=2(a+h)+2                                      (just replace x in a+h)

g(a+h)-g(a)=(2(a+h)+2)-(2a+2)

                    =(2a+2h+2)-(2a+2)

                    =(2a+2h+2-2a-2)

                   = 2h

i.e. g(a+h)-g(a)=2h
answered Jan 8, 2013 by Justin Pupil
edited Jan 8, 2013 by Justin
+1 vote
given that

g(x)=2x+2

g(a)=2a+2                                                 (just replace x in a)

g(a+h)=2(a+h)+2                                      (just replace x in a+h)

g(a+h)-g(a)=(2(a+h)+2)-(2a+2)

                     =(2a+2h+2)-(2a+2)

                     =(2a+2h+2-2a-2)

                     = 2h

there fore  g(a+h)-g(a)=2h
answered Jan 9, 2013 by richardson Scholar

Related questions

asked Jan 9, 2015 in CALCULUS by anonymous
...